Fungi Classification using Convolution Neural Network - et. al., Sukanya S. Gaikwad, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents a model based on Convolution Neural Network (CNN) to identify and classify the fungi those causes disease to apple plant leaf. In this paper, apple scab, rust, black rot, and healthy leaf are studied and classified. The plant pathology dataset (publically available) consists of 9164 images are used for experimentation. The proposed CNN model identifies and classifies the apple leaves into these four categories. This model can successfully detect and classify diseases with an accuracy of 88.9%.